Comparative Study of Different Methods to Determine the Role of Reactive Oxygen Species Induced by Zinc Oxide Nanoparticles - Najim, Nigar A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2015)
Accumulation of reactive oxygen species (ROS) followed by an increase in oxidative stress is associated with cellular responses to nanoparticle induced cell damages. Finding the best method for assessing intracellular ROS production is the key step in the detection of oxidative stress induced injury. This study evaluates and compares four different methods for the measurement of intracellular ROS generation using fluorogenic probe, 2´,7´-dichlorofluorescein diacetate (DCFH-DA). Hydrogen peroxide (H2O2) was utilised as a positive control to assess the reactivity of the probe. Spherically shaped zinc oxide (ZnO) nanoparticles with an average particle size of 85.7 nm were used to determine the diverse roles of ROS in nanotoxicity in Hs888Lu and U937 cell lines. The results showed that different methods exhibit different patterns of ROS measurement. In conclusion this study found that the time point at which the DCFH-DA is added to the reaction, the incubation time and the oxidative species that is responsible for the oxidation of DCFH, have impact on the intracellular ROS measurement.